Habitat Fragmentation Differentially Affects Genetic Variation, Phenotypic Plasticity and Survival in Populations of a Gypsum Endemic - Matesanz, Silvia; Rubio Teso, María Luisa; García-Fernández, Alfredo; Escudero, Adrián (Frontiers in Plant Science, 2017)
Abstract Habitat fragmentation, i.e., fragment size and isolation, can differentially alter patterns of neutral and quantitative genetic variation, fitness and phenotypic plasticity of plant populations, but their effects have rarely been tested simultaneously. We assessed the combined effects of size and connectivity on these aspects of genetic and phenotypic variation in populations of Centaurea hyssopifolia, a narrow endemic gypsophile that previously showed performance differences associated with fragmentation. We grew 111 maternal families sampled from ten populations that differed in their fragment size and connectivity in a common garden, and characterized quantitative genetic variation, phenotypic plasticity to drought for key functional traits, and plant survival, as a measure of population fitness. We also assessed neutral genetic variation within and among populations using eight microsatellite markers. Although Centaurea hyssopifolia is a narrow endemic gypsophile, we found substantial neutral genetic variation and quantitative variation for key functional traits. The partition of genetic variance indicated that a higher proportion of variation was found within populations, which is also consistent with low population differentiation in molecular markers, functional traits and their plasticity. This, combined with the generally small effect of habitat fragmentation suggests that gene flow among populations is not restricted, despite large differences in fragment size and isolation. Importantly, population’s similarities in genetic variation and plasticity did not reflect the lower survival observed in isolated populations. Overall, our results indicate that, although the species consists of genetically variable populations able to express functional plasticity, such aspects of adaptive potential may not always reflect populations’ survival. Given the differential effects of habitat connectivity on functional traits, genetic variation and fitness, our study highlights the need to shift the focus of fragmentation studies to the mechanisms that regulate connectivity effects, and call for caution on the use of genetic variation and plasticity to forecast population performance.